“Hybrid Peacebuilding in Gaza: Role of the Board of Peace” - Simanjuntak, Peronika; Octavian, Ardy; Dalia, Carmelita; Novianty, Rara; Arswenda, Arnold; Azizah, Rahmalia Wulan; Ramadina, Trisni Salsa (CV. Dalle’ Deceng Abeeayla, 2026)
This study aims to evaluate the strategic role of the Board of Peace (BoP) as a network-based governance model in accelerating infrastructure recovery in the Gaza conflict zone. Utilizing an explanatory case study method with a qualitative approach, this research gathers data through in-depth interviews with relevant stakeholders and an analysis of global reports. The findings demonstrate that the